Money and Other Measurement Systems - Denis Rodin; Anton Sukhoverkhov (Journal of Economic Sociology, 2025)
The authors examine the origin, development and nature of money as a special measuring sign system. Historical examples show that the value of first commodity money and goods themselves was determined by weight or volume, with commodity money used as a standard for these measures. The paper provides a comparative analysis of commodity (evolutionary) theories and institutional theories regarding the origin of money as “units of account” and “medium of exchange.” Modern fiat money acquired purchasing power as representatives (substitutes) of real commodity money. However, with the abolition of the gold standard in the second half of the twentieth century, fiat money became conventional, symbolic, and unbacked signs whose value is based on trust in the issuer and on exchange value determined by supply and demand. The article argues that the transition to fiat money led to the deficiency of a stable standard for measuring value and increased the role of emotional factors in valuation (measurement). It is shown that in the modern economy, in addition to supply and demand, popularity as “generalized symbolic medium” becomes a significant factor in the determining value. It has become both a new social measure of economic value and an intangible asset that can be “traded” and “exchanged” for other assets. Traditional measures of value, such as intrinsic value or the value of money determined by the government, are accompanied by “perceived value.” In this regard, the research proposes the concept of irrational or emotional prerequisites for the emergence of certain types of commodity money. The article also reveals the importance of time as a medium of exchange and a value measurement system. The article proposes further development of commodity currency circulation (for example, energy currency) and argues for the need to return to commodity-backed currencies in order to maintain economic stability and create a competitive advantage for the ruble as a possible global reserve currency.